Laboratory and field efficacy of natural products against the invasive pest Halyomorpha halys and side effects on the biocontrol agent Trissolcus japonicus - Elena Chierici; Elisa Marchetti; Adriana Poccia; Antonio Russo; Vito Antonio Giannuzzi; Lorenzo Governatori; Luca Zucchi; Gabriele Rondoni; Eric Conti (Scientific Reports)
Abstract The brown marmorated stink bug, Halyomorpha halys (Hemiptera: Pentatomidae), is an invasive pest causing major economic losses to crops. Since its outbreaks in North America and Europe, H. halys has been controlled with synthetic pesticides. More sustainable methods have been proposed, including biocontrol and use of natural products. Here, we conducted laboratory and field investigations to evaluate organically registered products for their effectiveness against H. halys and their non-target effect on the egg parasitoid, Trissolcus japonicus (Hymenoptera: Scelionidae). In the laboratory, azadirachtin, orange oil, potassium salts of fatty acids, kaolin, basalt dust, diatomaceous earth, zeolite, sulphur formulations, calcium polysulfide, and mixtures of sulphurs plus diatomaceous earth or zeolite demonstrated higher lethality against H. halys nymphs compared to control. Calcium polysulfide, azadirachtin and sulphur achieved more than 50% mortality. All treatments except azadirachtin and kaolin had negative effects on T. japonicus, with mortality exceeding 80% for calcium polysulfide and sulphur. Field experiments were conducted in 2021 and 2022 in pear orchards. Diatomaceous earth alone or alternated with sulphur or calcium polysulfide provided similar H. halys control, when compared to farm strategies based mostly on neonicotinoid (acetamiprid) treatments. Implications for H. halys control in integrated pest management are discussed.